Bacteriomimetic liposomes improve antibiotic activity of a novel energy-coupling factor transporter inhibitor - Drost, Menka; Diamanti, Eleonora; Fuhrmann, Kathrin; Goes, Adriely; Shams, Atanaz; Haupenthal, Jörg; Koch, Marcus; Hirsch, Anna K.H.; Fuhrmann, Gregor (Pharmaceutics, 2022)
Liposomes have been studied for decades as nanoparticulate drug delivery systems for cytostatics, and more recently, for antibiotics. Such nanoantibiotics show improved antibacterial efficacy compared to the free drug and can be effective despite bacterial recalcitrance. In this work, we present a loading method of bacteriomimetic liposomes for a novel, hydrophobic compound (HIPS5031) inhibiting energy-coupling factor transporters (ECF transporters), an underexplored antimicrobial target. The liposomes were composed of DOPG (18:1 (∆9-cis) phosphatidylglycerol) and CL (cardiolipin), resembling the cell membrane of Gram-positive Staphylococcus aureus and Streptococcus pneumoniae, and enriched with cholesterol (Chol). The size and polydispersity of the DOPG/CL/± Chol liposomes remained stable over 8 weeks when stored at 4◦ C. Loading of the ECF transporter inhibitor was achieved by thin film hydration and led to a high encapsulation efficiency of 33.19% ± 9.5% into the DOPG/CL/Chol liposomes compared to the phosphatidylcholine liposomes (DMPC/DPPC). Bacterial growth inhibition assays on the model organism Bacillus subtilis revealed liposomal HIPS5031 as superior to the free drug, showing a 3.5-fold reduction in CFU/mL at a concentration of 9.64 µM. Liposomal HIPS5031 was also shown to reduce B. subtilis biofilm. Our findings present an explorative basis for bacteriomimetic liposomes as a strategy against drug-resistant pathogens by surpassing the drug-formulation barriers of innovative, yet unfavorably hydrophobic, antibiotics.
CRIS-Team Scopus Importer:2022-01-07
Keywords: Antibiotic resistance; Bacillus subtilis; Bacteriomimetic; Cardiolipin; Energy-coupling factor (ECF) transporters; Liposomes; Nanoantibiotics

Biocompatible bacteria-derived vesicles show inherent antimicrobial activity - Schulz, Eilien; Goes, Adriely; Garcia, Ronald; Panter, Fabian; Koch, Marcus; Mueller, Rolf; Fuhrmann, Kathrin; Fuhrmann, Gregor (Journal of Controlled Release, 2018)
Up to 25,000 people die each year from resistant infections in Europe alone, with increasing incidence. It is estimated that a continued rise in bacterial resistance by 2050 would lead up to 10 million annual deaths worldwide, exceeding the incidence of cancer deaths. Although the design of new antibiotics is still one way to tackle the problem, pharmaceutical companies investigate far less into new drugs than 30 years ago. Incorporation of antibiotics into nanoparticle drug carriers (“nanoantibiotics”) is currently investigated as a promising strategy to make existing antibiotics regain antimicrobial strength and overcome certain types of microbial drug resistance. Many of these synthetic systems enhance the antimicrobial effect of drugs by protecting antibiotics from degradation and reducing their side effects. Nevertheless, they often cannot selectively target pathogenic bacteria and – due to their synthetic origin – may induce side-effects themselves. In this work, we present the characterisation of naturally derived outer membrane vesicles (OMVs) as biocompatible and inherently antibiotic drug carriers. We isolated OMVs from two representative strains of myxobacteria, Cystobacter velatus Cbv34 and Sorangiineae species strain SBSr073, a bacterial order with the ability of lysing other bacterial strains and currently investigated as sources of new secondary metabolites. We investigated the myxobacterias’ inherent antibacterial properties after isolation by differential centrifugation and purification by size-exclusion chromatography. OMVs have an average size range of 145–194 nm. We characterised their morphology by electron cryomicroscopy and found that OMVs are biocompatible with epithelial cells and differentiated macrophages. They showed a low endotoxin activity comparable to those of control samples, indicating a low acute inflammatory potential. In addition, OMVs showed inherent stability under different storage conditions, including 4 °C, −20 °C, −80 °C and freeze-drying. OMV uptake in Gram-negative model bacterium Escherichia coli (E. coli) showed similar to better incorporation than liposome controls, indicating the OMVs may interact with model bacteria via membrane fusion. Bacterial uptake correlated with antimicrobial activity of OMVs as measured by growth inhibition of E. coli. OMVs from Cbv34 inhibited growth of E. coli to a comparable extent as the clinically established antibiotic gentamicin. Liquid-chromatography coupled mass spectrometry analyses revealed the presence of cystobactamids in OMVs, inhibitors of bacterial topoisomerase currently studied to treat different Gram-negative and Gram-positive pathogens. This work, may serve as an important basis for further evaluation of OMVs derived from myxobacteria as novel therapeutic delivery systems against bacterial infections.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Biogenic drug carriers; Electron cryomicroscopy; Extracellular vesicles; Myxobacteria; Nanoantibiotics; Outer membrane vesicles

Corrigendum to biocompatible bacteria-derived vesicles show inherent antimicrobial activity (Journal of Controlled Release (2018) 290 (46–55), (S0168365918305698) (10.1016/j.jconrel.2018.09.030)) - Schulz, Eilien; Goes, Adriely; Garcia, Ronald; Panter, Fabian; Koch, Marcus; Mueller, Rolf; Fuhrmann, Kathrin; Fuhrmann, Gregor (Journal of Controlled Release, 2019)
The authors regret that there was a mistake in calculating the number of outer membrane vesicles incubated with each cell. On page 48, paragraph 2.5., line 25, it should read “and the cells were incubated with 10, 100, 1,000 and 10,000 purified OMVs” and page 51, paragraph 3.2., line 13, should read “concentrations of 10,000 OMVs/cell no cytotoxic effects were observed”. According to this, Figs. 3 and S3 were modified. These errors do not change the conclusions published in this work. The authors also regret to correct that bacto peptone and not soy peptone was used for the preparation of M-medium (page 47, paragraph 2.1., line 6). The authors would like to apologise for any inconvenience caused.
CRIS-Team Scopus Importer:2021-06-29

Evaluation of the storage stability of extracellular vesicles - Richter, Maximilian; Fuhrmann, Kathrin; Fuhrmann, Gregor (Journal of Visualized Experiments, 2019)
Extracellular vesicles (EVs) are promising targets in current research, to be used as drugs, drug-carriers, and biomarkers. For their clinical development, not only their pharmaceutical activity is important but also their production needs to be evaluated. In this context, research focuses on the isolation of EVs, their characterization, and their storage. The present manuscript aims at providing a facile procedure for the assessment of the effect of different storage conditions on EVs, without genetic manipulation or specific functional assays. This makes it possible to quickly get a first impression of the stability of EVs under a given storage condition, and EVs derived from different cell sources can be compared easily. The stability measurement is based on the physicochemical parameters of the EVs (size, particle concentration, and morphology) and the preservation of the activity of their cargo. The latter is assessed by the saponin-mediated encapsulation of the enzyme beta-glucuronidase into the EVs. Glucuronidase acts as a surrogate and allows for an easy quantification via the cleavage of a fluorescent reporter molecule. The present protocol could be a tool for researchers in the search for storage conditions that optimally retain EV properties to advance EV research toward clinical application.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Asymmetric flow field-flow fractionation; Bioengineering; Enzyme encapsulation; Exosomes; Extracellular vesicles; Freeze-drying; Issue 147; Lyophilisation; Storage stability

Extracellular vesicles protect glucuronidase model enzymes during freeze-drying - Frank, Julia; Richter, Maximilian; De Rossi, Chiara; Lehr, Claus-Michael; Fuhrmann, Kathrin; Fuhrmann, Gregor (Scientific Reports, 2018)
Extracellular vesicles (EVs) are natural nanoparticles that play important roles in intercellular communication and are increasingly studied for biosignalling, pathogenesis and therapy. Nevertheless, little is known about optimal conditions for their transfer and storage, and the potential impact on preserving EV-loaded cargoes. We present the first comprehensive stability assessment of different widely available types of EVs during various storage conditions including −80 °C, 4 °C, room temperature, and freeze-drying (lyophilisation). Lyophilisation of EVs would allow easy handling at room temperature and thus significantly enhance their expanded investigation. A model enzyme, β-glucuronidase, was loaded into different types of EVs derived from mesenchymal stem cells, endothelial cells and cancer cells. Using asymmetric flow field-flow fractionation we proved that the model enzyme is indeed stably encapsulated into EVs. When assessing enzyme activity as indicator for EV stability, and in comparison to liposomes, we show that EVs are intrinsically stable during lyophilisation, an effect further enhanced by cryoprotectants. Our findings provide new insight for exploring lyophilisation as a novel storage modality and we create an important basis for standardised and advanced EV applications in biomedical research.
CRIS-Team Scopus Importer:2021-06-29

Integriertes Klimaschutzkonzept - Fuhrmann, Kathrin (2024)
Die Friedrich-Alexander-Universität Erlangen-Nürnberg (FAU) bearbeitet Nachhaltigkeit als Querschnittsthema über alle Handlungsfelder und integriert die Nachhaltigkeitsziele der Vereinten Nationen (SDGs) in ihre Mission und Aktivitäten. Sie denkt Nachhaltigkeit ganzheitlich in den drei Dimensionen „Ökonomie“, „Ökologie“ und „Soziales“. Trotz anspruchsvoller Rahmenbedingungen, möchte die FAU als Volluniversität mit starker Verwurzelung in der gesamten Region bei der Umsetzung erfolgreichen Klimaschutzes als Vorbild agieren. Die FAU sieht es als ihre gesellschaftliche Verantwortung, durch einen Ausbau ihrer bisherigen Aktivitäten im Bereich Klimaschutz und eine umfassende Reduktion der eigenen Treibhausgas (THG)-Emissionen ihren Beitrag zur Bekämpfung des Klimawandels zu leisten. Aus diesem Grund hat sie ein integriertes Klimaschutzkonzept erstellt, welches als Grundlage für die systematische und strukturierte Reduktion der Treibhausgas (THG)-Emissionen der FAU dienen soll.<br
Keywords: Klimaschutz; Klimaschutzkonzept

Recent advances in oral delivery of macromolecular drugs and benefits of polymer conjugation - Fuhrmann, Kathrin; Fuhrmann, Gregor (Current Opinion in Colloid & Interface Science, 2017)
Oral administration of drugs is a two-edged sword – on one hand it is a non-invasive and easy-to-handle administration of drugs, on the other hand macromolecular pharmaceutical compounds cannot easily cross the epithelial barrier to reach systemic circulation or they could be inactivated in the gastrointestinal tract. Due the latter's nature with pH variations and proteolytic enzymes which digest and degrade external compounds, in particular peptides and proteins, oral delivery of macromolecular substances is an ongoing challenge in the field of pharmaceutical research. Several avenues of overcoming these drawbacks have been evaluated in the past, among them the promising approach of conjugation to natural and synthetic polymers. Polymers provide protection under harsh gastrointestinal conditions, may further enhance macromolecular drug absorption and pharmacological activity, and thus augment therapeutic efficiency. This short review highlights state-of-the-art developments in the field of oral macromolecule delivery and the benefit of polymer conjugation. We focus on a main review period from 2012 to 2017, and critically discuss latest developments for macromolecule engineering.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Biomimetics; Enzyme therapy; Gastrointestinal tract; Oral proteins; Polymer therapeutics; Surface engineering

The inherent antibiotic activity of myxobacteria-derived autofluorescent outer membrane vesicles is switched on and off by light stimulation - Lapuhs, Philipp; Heinrich, Eilien; Garcia, Ronald; Goes, Adriely; Frank, Nicolas; Bollenbach, Lukas; Stibane, Veronika; Kuhn, Thomas; Koch, Marcus; Kiemer, Alexandra K.; Müller, Rolf; Fuhrmann, Kathrin; et al. (Nanoscale, 2022)
Outer membrane vesicles are small, lipid-based vesicles shed from the outer membrane of Gram-negative bacteria. They are becoming increasingly recognised as important factors for resistance gene transfer, bacterial virulence factors and host cell modulation. The presence of pathogenic factors and antimicrobial compounds in bacterial vesicles has been proven in recent years, but it remains unclear, if and how environmental factors, such as light specifically regulate the vesicle composition. We report the first example of autofluorescent vesicles derived from non-pathogenic soil-living myxobacteria. These vesicles additionally showed inherent antibiotic activity, a property that is specifically regulated by light stimulation of the producing bacteria. Our data provide a central basis for better understanding the environmental impact on bacteria-derived vesicles, and design of future therapeutic options.
CRIS-Team Scopus Importer:2022-12-09

Tracking matricellular protein SPARC in extracellular vesicles as a non-destructive method to evaluate lipid-based antifibrotic treatments - Zivko, Cristina; Fuhrmann, Kathrin; Fuhrmann, Gregor; Luciani, Paola (Communications Biology, 2022)
Uncovering the complex cellular mechanisms underlying hepatic fibrogenesis could expedite the development of effective treatments and noninvasive diagnosis for liver fibrosis. The biochemical complexity of extracellular vesicles (EVs) and their role in intercellular communication make them an attractive tool to look for biomarkers as potential alternative to liver biopsies. We developed a solid set of methods to isolate and characterize EVs from differently treated human hepatic stellate cell (HSC) line LX-2, and we investigated their biological effect onto naïve LX-2, proving that EVs do play an active role in fibrogenesis. We mined our proteomic data for EV-associated proteins whose expression correlated with HSC treatment, choosing the matricellular protein SPARC as proof-of-concept for the feasibility of fluorescence nanoparticle-tracking analysis to determine an EV-based HSCs’ fibrogenic phenotype. We thus used EVs to directly evaluate the efficacy of treatment with S80, a polyenylphosphatidylcholines-rich lipid, finding that S80 reduces the relative presence of SPARC-positive EVs. Here we correlated the cellular response to lipid-based antifibrotic treatment to the relative presence of a candidate protein marker associated with the released EVs. Along with providing insights into polyenylphosphatidylcholines treatments, our findings pave the way for precise and less invasive diagnostic analyses of hepatic fibrogenesis.
CRIS-Team Scopus Importer:2022-11-11